"Give Peace a Chance?: The Anti-War Movement and the Arab-Israeli Conflict". Issue 2 (2nd July 2020) - Fischbach, Michael R.
ABSTRACT: This study examines the anti-war movement's conflicted attitude toward the Arab-Israeli conflict in the late 1960s and early 1970s. It details how these uncertainties highlighted and exacerbated several fault lines, including between those advocating the single-issue approach versus those wishing to expand the movement's focus beyond Vietnam, and between anti-imperialists who denounced Israel versus others who supported it. This friction over the Middle East was a microcosm of much deeper tensions that bedeviled and weakened the entire liberal-to-left-wing spectrum of American politics, and its examination reveals much about the weaknesses and struggles facing progressives five decades ago and even today.